The Perception of Respondents of Packaging Innovations in Slovakia - Loucanova, Erika; Parobek, Jan; Kalamarova, Martina (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2016)
The paper deals with the evaluation of the perception of packaging innovations in terms of their functions through the Kano model. It focuses on the evaluation of the perception of innovation of all main seven functions of packaging, in particular on handling, protective, informative, economic, environmental, promotional and ecological packaging functions. The results indicate that the target groups interested in the new innovative packaging are mostly in age between 41 to 60 years. These groups have the highest requirements for new packaging. The innovations of handling functions of packaging have the most significant influence on the older generation. However, almost all ages categories positively recognize ecological innovations of packaging.